Haiti : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2009)
The Haitian authorities have launched a series of actions with the aim of executing the reforms, for which quantitative and qualitative performance criteria have been set and point to the achievement of noteworthy progress. The progress report on Haiti's Poverty Reduction Strategy Paper is also discussed. The outcomes of the reforms suggest that Haiti has made significant progress toward achievement of the completion point under the Heavily Indebted Poor Countries Initiative, supported by the Poverty Reduction and Growth Facility.